Effect of different mineralizers in the sonochemical synthesis of self-assembled nanorods vanadium oxide - Yap, Taufiq Yun Hin; Hoh, Joshua J. R.; Wong, Yee Ching (Asian Publication Corporation, 2011)
The effects of different potassium salts (KNO(3) and KCl) as mineralizer on the synthesis of self-assembled nanorods vanadium pentoxide, V(2)O(5) via sonochemical treatment were studied at different duration i.e., 30, 60, 90 and 120 min. All the materials synthesized were further characterized by x-ray diffraction, scanning electron microscopy and transmission electron microscopy. X-ray diffraction patterns revealed that the potassium ion from the mineralizers reacted with the V(2)O(5) after prolonged sonochemical treatment duration. The morphology of the V(2)O(5) changed from platelet-like structures into nanorods after 90 min of sonochemical treatment. TEM micrographs show the process of formation of the self-assembled V(2)O(5) nanorod bundles with increased sonochemical treatment duration.